PENGARUH PERAN GANDA (WORK FAMILY CONFLICT) DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PERAWAT RS DR. HI. ABDUL MOELOEK PROVINSI LAMPUNG - Pratama, Rizki Mupty; Rahayu, Sri; Muprihan, Muprihan (STMIK Pringsewu, 2025)
This study aims to determine the effect of Dual Roles on employee performance in Hospital Nurses. Hi. Abdul Moeloek, The Effect of Emotional Intelligence on Employee Performance in Hospital Nurses. Hi. Abdul Moeloek, The Effect of Dual Roles and Emotional Intelligence on Employee Performance in Hospital Nurses. Hi. Abdul Moeloek. The type of research used in this study is quantitative research with associative methods. The data source used is primary data with the data collection method being a field collection method in the form of questionnaire distribution. The population in this study is all hospital nurses. Hi. Abdul Moeloek, who amounted to 243 female nurses using a sample of all employees totaling 50 nurses. The sampling technique in this study is Purposive Sampling, which is a sampling method based on certain considerations. The instrument requirements test used are the validity test and the reliability test. The data analysis requirements test used is the linearity test, the multicollinearity test. The data analysis method uses multiple linear regression. And the hypothesis test used is the T test and the F test. Abdul Moeloek Lampung Province, Emotional Intelligence affects the Performance of Nurses at Dr.Hi.Abdul Moeloek Hospital, Lampung Province, Dual Role and Emotional Intelligence affect the Performance of Nurses at Dr.Hi.Abdul Moeloek Hospital, Lampung Province.